A novel Bacillus sp. isolated from rotten seaweed: Identification and characterization alginate lyase its produced (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Zilda DS, Yulianti Y, Sholihah RF, Subaryono S, Fawzya YN, Irianto HE.2019. A novel Bacillus sp. isolated from rotten seaweed: identification and characterization alginate lyase its produced. Biodiversitas 20: 1166-1172. Alginate lyase has been known as potential biocatalyst not only for industrial but also medicinal application especially for the production of oligosaccharides which have distinct bioactivities. An alginate lyase, AlgT513, has been isolated from rotten seaweed bacterium strain T513 and characterized. The bacterium showed low similarity (95%) with Bacillus tequilensis strain 10b based on 16S rDNA sequence indicating that AlgT513may be a novel Bacillus species. The bacterium forms a clear zone on solid medium with 0.5% sodium alginate addition. The optimum temperature and pH were 50ºC and 8 respectively. AlgT513 maintained stability at board pHs of 4-9 and temperature of 45ºC. Metal ions Mg2+, Ca2+ and K+ increase the activity of the enzyme while Zn2+, Co2+ and Li+ strongly inhibit it. NaCl inhibits AlgT513 activity where most of the alginate lyases need it to reach maximum activity. AlgT513 is suggested as a serine metalloenzyme due to inhibition of ethylenediaminetetraacetic acid (EDTA) and phenylmethylsulfonyl fluoride (PMSF).
Keywords: Alginate Lyase, AlgT513, Bacillus sp., rotten seaweed